Directive Speech Acts and Wisdom Values in Q.S. Al Mu’min (A Pragmatics Study) - Sholichatul Bisriyah (Institut Agama Islam Negeri Salatiga, 2022)
This paper aims to examine the directive speech acts form and the wisdom values in Q.S. Al Mu’min. This is qualitative research applying library research design. Using the Qur’an published by PT Surya Prisma Sinergi in 2012, the research data is in the form of sentence structure of directive speech acts. The results found as many as 75 forms of directive speech acts, with the classification of 25 types of directive speech acts of command, 9 types of directive speech acts of prohibition, 6 types of directive speech acts of request, 4 types of directive speech acts of the question, and 31 types of directive speech acts of advice. Furthermore, it was found that the types of directive speech acts of request with the function of begging and asking; the question with the function of asking; command with the function of commanding, requiring, and ordering; prohibition with the function of prohibiting; and advice with the function of advising, calling, warning, and reminding. In addition, there are found wisdom values, in 13 verses over 85 verses, including courage, firmness of faith, non-abusive power, empathy, and tawakkal.